Teoría e impropiedad en M. Heidegger (1923-1927): el problema de los discursos objetivantes - Bertorello, Adrián (Logos. Anales del Seminario de Metafísica, 2007)
The purpose of this study is to determine Heidegger’s dominant position in front of the relationship between existence improper modality and theory. From the ambivalence of this issue in Sein und Zeit, the study goes through the different lectures of the Marburg period where Heidegger talks about this same issue. The text examines Heidegger’s explanation of the phenomenological notion of conscience and the Aristotelian concepts “sofía”, “dóxa” and “episteme” in order to establish Heidegger’s dominant position in relation to the improper origin of these theoretical concepts.